STUDY OF RUNWAY DEVELOPMENT AT SUPADIO PONTIANAK INTERNATIONAL AIRPORT ON THE OPERATION OF A330-300 AIRCRAFT - Muhammad Wartino (Institut Teknologi Dirgantara Adisutjipto, 2020)
Modes of air transportation are also an option for making Hajj and Umrah trips in Indonesia. At this time the Supadio International Airport is extending the runway which was originally 2250 meters to 2600 meters. So, it is expected to be able to operate A330-300 aircraft for Hajj and Umrah flights. The method used in this research uses the calculation of ARFL (Aerodrome Reference Field Length), ACN-PCN (Aircraft Classification Number-Pavement Classification Number), runway width analysis and runway strips analysis From the results of research and analysis conducted with the runway extension of 2600m × 45m with runway shoulders 2m and PCN number 51/F/D/X/T A330-300 aircraft cannot operate at Supadio International Airport. So, that the runway development needs to be developed to 3097m × 45m with runway shoulders 7,5m and PCN number of 89/F/D/X/T. So, that A330- 300 aircraft can operate for Hajj flights in Pontianak